Conflicts and creative idea endorsement: Do subordinates' political skills and implementation instrumentality matter?. Issue 5 (17th July 2019) - Adeel, Ahmad; Pengcheng, Zhang; Saleem, Farida; Ali, Rizwan; Batool, Samreen
Abstract : Purpose: This paper aims to investigate relationship conflicts and creative idea endorsement to develop the understanding of managerial reactions towards ideas of those who develop relationship conflicts with managers/supervisors at work. Taking a contingency perspective, the authors also investigated role subordinates' political skills and implementation instrumentality play in determining supervisors' endorsement of subordinates' creative ideas. Design/methodology/approach: The authors used two sources of data collected from 243 subordinates and their respective 41 supervisors of a multinational software company operating in an emerging economy (Pakistan) and analyzed the hypothesized model with Mplus using random coefficient modeling. Findings: With this research, the authors contributed to management literature by investigating how the effects of relationship conflicts on creative idea endorsement depend on subordinates' political skills and implementation instrumentality. They postulate a negative relationship between relationship conflict and creative ideas endorsement and predict that this negative relationship is augmented by subordinates' implementation instrumentality but attenuated by subordinates' political skills. They also give directions to decision makers in organizations that they must inform the managers/supervisors about negative effects of their relationship conflict with their subordinates and train supervisors and subordinates about reducing their relationship conflicts with each other for mutual benefits. Originality/value: Organizations should take a relationship perspective when creating an environment for creativity: an environment based on mutual trust and respect so that exchange relationships can foster. With this research, the authors extended the list of potential detriment associated with relationship conflicts, that is the endorsement of creative ideas by supervisors. The authors also extended creativity literature by investigating social relationships for selection-focused creativity (idea endorsement) instead of variance-focused creativity (idea generation).